DESIGNING 'KIDDOCARE' APPLICATION FOR PEDIATRIC NURSING PRACTICE WITH USER CENTERED DESIGN (UCD) - Rifa Yanti; Dasril Aldo; Nursaka Putra; Dading Qolbu Adi; Miftahul Ilmi (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
This research aims to develop KiddoCare, a mobile-based pediatric nursing application designed using the User Centered Design (UCD) method. The methodology used in this study included interviews, questionnaire distribution, and documentation with the aim of filling the gap of tools and applications that specifically meet the unique needs in pediatric care. Interviews with health workers showed that one of the biggest challenges was the lack of efficient communication between nurses and parents, as well as difficult access to pediatric health information. Therefore, this app is designed to improve communication between nurses and pediatric patients and facilitate access to important health information. The UCD process includes understanding the user context, determining user needs, designing and producing solutions, and evaluating those needs. From the initial survey of 74 respondents, 50.56% agreed and 46.02% strongly agreed with the need for easier access to pediatric health information. A total of 74 respondents evaluated the app and gave positive feedback; 47.01% 'agreed', 41.17% 'strongly agreed' with the functionality of the app, and 11.82% 'moderately'. No respondents expressed 'disagree' or 'strongly disagree'. In conclusion, KiddoCare was rated as an effective and appropriate pediatric nursing tool, supporting flexible care that is adaptive to each child's individual needs.